Blockchain transactions as a promising mechanism to ensure sustainable development of the construction complex under sanctions (by the example of the Russian economy) - M. R. Safiullin; L. A. Elshin; A. A. Dinmukhametova; A. R. Sharapov (Vestnik MGSU)
Introduction. Restrictions imposed by Western countries on the access of the Russian financial system to international clearing systems significantly complicate the development of economic sectors that are deeply integrated into international supply chains. Among them, it is necessary to single out the construction industry, which acts as a “locomotive” for the development of many other types of economic activity. This paper is devoted to the review of emerging macroeconomic effects in the context of leveling the risks of the growth dynamics of the construction industry of the Russian Federation within the framework of the transition of the national payment system to blockchain (DLT) in the context of solving the issue of import substitution. The subject of the study is the features of the prospects for sustainable development of the Russian economy in the context of adjusting the import of construction materials.Materials and methods. The tools of building a system of recursive equations estimating macroeconomic externalities in the process of simulation modelling of blockchain use in the system of ensuring sustainable settlements with foreign counterparties, as well as correlation and regression analysis, which forms the basis for identifying the impact of the Russian construction industry on the prospects for GDP growth were applied.Results. The short-term potential of possible slowdown of Russia’s GDP growth (–0.45 % per year) as part of the localization of import supplies of building materials. It is substantiated that the risks of limiting the supply of building materials can be ensured through the introduction of blockchain technologies into the system of cross-border payments of the Russian Federation, which form a new basis for the movement of cash flows.Conclusions. The value of the obtained research results consists in the identified and empirically substantiated risks of slowing down the development of the construction industry and the national economy of the Russian Federation as a whole within the framework of possible localization of supplies of building materials from abroad as a result of sanctions pressure on financial markets. It is substantiated that the creation of regional blockchain platforms on a global scale can act as a tool for leveling risks, providing the possibility of stability and independence of the formation of transnational supply chains from global clearing services.